Profile of Non-Melanoma Skin Cancer and Malignant Melanoma at Dr. Mohammad Hoesin General Hospital Palembang from 2017 - 2019: A Retrospective Study - Yulia Farida Yahya; Odelia Jovita Jusuf Fantoni; Susanti Budiamal; Theresia L. Toruan (HM Publisher, 2022)
Background: Currently, there is an increasing trend in skin cancer incidence, especially non-melanoma skin cancer (NMSC), including basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), also malignant melanoma (MM), causing an increase in morbidity and mortality rates. The high treatment cost causes an economic burden of disease in the country and negatively impacts public health issues. This study aimed to determine the profile of NMSC and MM regarding the sex, age, occupation, location of the lesion, clinicohistopathological diagnosis of skin cancer in Dr. Mohammad Hoesin General Hospital Palembang January 2017-December 2019. Methods: A retrospective analytical observational study obtained from medical records of NMSC and MM patients in Dr. Mohammad Hoesin General Hospital Palembang from January 2017-December 2019 as confirmed using histopathological results from the Pathology Department. Results: There were 324 new cases of NMSC and MM, including BCC 162 cases (50%) and SCC 130 cases (40.1%), whereas MM 32 cases (9.9%). Women had a higher probability of developing skin cancer with a ratio of 1.13:1. The average age of skin cancer was between 55-64 years old (33.6%), with a mean age of 57 years old. There was a statistically significant relationship between gender, age, occupation, and areas of skin cancer against skin cancer. Furthermore, overexposure to ultraviolet (UV) radiation is related to high-risk occupations, including farmers (50%), while the most frequent location of skin cancer was the face (67.3%). Conclusion: Our study implicated a 1.5-fold increase in new cases of skin cancer between 2017 to 2019. BCC cases were more prevalent than SCC and MM cases. There was also a significant association between skin cancer and occupation also the location of skin cancer as the risk factor for UV exposure. Nevertheless, further research involving larger samples or a multicenter approach is needed.